2006
DOI: 10.1111/j.1525-139x.2006.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Dialyzer Reuse—Part II: Advantages and Disadvantages

Abstract: Although single dialyzer use and reuse by chemical reprocessing are both associated with some complications, there is no definitive advantage to either in this respect. Some complications occur mainly at the first use of a dialyzer: a new cellophane or cuprophane membrane may activate the complement system, or a noxious agent may be introduced to the dialyzer during production or generated during storage. These agents may not be completely removed during the routine rinsing procedure. The reuse of dialyzers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 72 publications
1
28
0
5
Order By: Relevance
“…154 The membrane serves both structural and protective functions as humoral and cellular immune components are excluded from the cultured nor is there any concomitant increase in mortality. [129][130][131][132] A recent study suggests reuse of dialyzers may convey a reduced mortality risk; however, this was a short study in a single center and caution is warranted regarding generalization of results. 133 Dialyzer reuse continues worldwide using predominantly chemical processing, most commonly peracetic acid and formaldehyde.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…154 The membrane serves both structural and protective functions as humoral and cellular immune components are excluded from the cultured nor is there any concomitant increase in mortality. [129][130][131][132] A recent study suggests reuse of dialyzers may convey a reduced mortality risk; however, this was a short study in a single center and caution is warranted regarding generalization of results. 133 Dialyzer reuse continues worldwide using predominantly chemical processing, most commonly peracetic acid and formaldehyde.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…The earliest studies reported increased mortality associated with reuse, but suggested that mortality was associated with the specific reprocessing agent and not reuse per se. Use of high-flux dialyzers became much more common in the late 1980s and early 1990s (1). Research from this period did not find an association between reuse and mortality risk ( Table 1).…”
Section: Introductionmentioning
confidence: 92%
“…Ethylene oxide has traditionally been implicated in this reaction, and the emergence of nonethylene oxide sterilization techniques has significantly reduced its occurrence (23). However, other chemical contaminants during the manufacturing process might pose some potential hazards if dialyzers are not preprocessed before first use, a common practice in dialysis centers that reuse.…”
Section: Potential Health Hazards Of Single-use Dialyzersmentioning
confidence: 99%
“…A number of potentially serious disadvantages of reusing dialyzers have previously been highlighted (6,23). Residual germicide infusion as a result of the rebound release of disinfectants during dialysis may have theoretical long-term adverse consequences on the patient's health.…”
Section: Disadvantages Of Dialyzer Reusementioning
confidence: 99%
See 1 more Smart Citation